The Late Bronze Age pastoralist settlement at Halehaxite in the Tianshan Mountains, Xinjiang, China, a zooarchaeological perspective. (October 2022) - Yu, Chong; You, Yue; Luo, Jiaming; Ruan, Qiurong
Highlights: Halehaxite provides the first zooarchaeological record from the East Tianshan Mountains in Late Bronze Age. Halehaxite is a pastoralist settlement and the herd is dominant by cattle, different from other contemporaneous sites in the surrounding regions. The majority of the herd was slaughtered before one-year-old, indicate a focus on the exploitation of meat and milk and less on wool and traction. The birth was deliberately controlled in spring, substantial kill happened in autumn. Abstract: Northwestern China is a key region for the exchange of population, commodity, technology, custom and culture between the east and west part of the Old World since prehistoric times. However, we lack zooarchaeological evidence from settlement sites in Xinjiang province, which makes it difficult to understand the pastoral economies and livestock herding activities of the Late Bronze Age in this area. Here, we present a study of the earliest and meanwhile the first systematic zooarchaeological analysis from the Late Bronze Age settlement, the Halehaxite site in northwestern Xinjiang. Our findings pointed out that the herd of Halehaxite comprises four domestic animals: cattle, sheep, goats and horses. The herd is dominated by cattle, different from other contemporaneous sites in the Central and East Tianshan Mountains. Mortality patterns of the domesticates were linked to sophisticated milk exploitation and not many individuals were kept for long-term secondary production.